Lattice-Preferred Orientation and Microstructures of Minerals and Their Implications for Seismic Anisotropy - Jung, Haemyeong; Park, Munjae (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The lattice-preferred orientation (LPO) of minerals is important for interpreting seismic anisotropy, which occurs in the Earth's crust and mantle, and for understanding the internal structure of the deep interior of the Earth. The characterization of microstructures, including LPO, grain size, grain shape, and misorientation, is important to determine the deformation conditions, deformation histories, kinematics, and seismic anisotropies in the crust and mantle The articles in this Special Issue prove that studies of LPO and microstructures of minerals and rocks are a major research area and provide a foundation for interpreting seismic anisotropy in the crust, mantle, and subduction zones. Therefore, the authors hope that this Special Issue encompassing recent advances in the measurement of LPOs of different minerals under various tectonic settings will be a fundamental and valuable resource for the readers and researchers interested in exploring the deformation conditions of minerals and rocks, as well as the interpretation of seismic anisotropy in the crust, mantle, and subduction zones.